Social Accountability in Health in Indonesia : Lessons from Programs - Bennouna, Cyril; Kusumaningrum, Santi; Siagian, Clara; Laugen, Chris (World Bank, Washington, DC, 2018)
This brief provides an overview of the most relevant programs promoting social accountability in Indonesia's primary health sector. It focuses on maternal and child health, and summarizes key global and regional lessons learned to inform social accountability initiatives in the country. A number of programs in Indonesia have increased citizens' access to information in the health sector and have empowered citizens to hold government accountable to basic health services. Some lessons include using multi-tool and multi-stakeholder approaches to social accountability strategies in order to reduce implementation risks in different contexts. Social accountability can reinforce programmatic gains by strengthening institutional mechanisms for problem solving.